2015
DOI: 10.1007/s10566-015-9341-y
|View full text |Cite
|
Sign up to set email alerts
|

Academic Aspirations as a Moderator of the Link Between Negative Life Events and Delinquency in a Sample of Latino Youth

Abstract: Background: Latino youth are one of the fastest growing populations in the United States

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…In line with the existing evidence (DiPierro et al, 2016; Freedy et al, 2010), we found differential associations between stressful life event types and proactive and reactive aggression. For example, witnessing interpersonal violence or sexual victimization was associated with higher levels of proactive and reactive aggression, witnessing other trauma exposure was associated with higher levels of reactive aggression only, and witnessing war zone exposure was not significantly correlated with either function of aggression.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In line with the existing evidence (DiPierro et al, 2016; Freedy et al, 2010), we found differential associations between stressful life event types and proactive and reactive aggression. For example, witnessing interpersonal violence or sexual victimization was associated with higher levels of proactive and reactive aggression, witnessing other trauma exposure was associated with higher levels of reactive aggression only, and witnessing war zone exposure was not significantly correlated with either function of aggression.…”
Section: Resultssupporting
confidence: 91%
“…However, despite accruing evidence and emerging theory, research examining the links between stressful life events and proactive and reactive aggression is limited as it has not investigated how stressful life event characteristics might influence aggressive behaviors. Evidence suggests that event characteristics, including level of exposure to and type of stressful life event, play an important role in determining an individual’s risk of maladaptive outcomes (DiPierro, Fite, Cooley, & Poquiz, 2016; Gil & Caspi, 2006). For example, rates of PTSD were approximately five times higher for individuals who had experienced a terrorist attack than those who were indirectly or not exposed to the event (Gil & Caspi, 2006).…”
mentioning
confidence: 99%
“…These results suggest that weak parental support reduces self-efficacy for future academic success, which, in turn, leaves a child vulnerable to the negative effects of delinquent peer associations. One possibility is that low self-efficacy for future academic success can make delinquent peers, who, as a group, tend to have low academic aspirations (DiPierro, Fite, Cooley, & Poquiz, 2016), more attractive to the individual. On a more positive note, it also means that strong parental support can enhance self-efficacy for academic success, which, in turn, protects the child against negative peer influence by making delinquent peers seem less attractive.…”
Section: Discussionmentioning
confidence: 99%
“…Latinx youth are overrepresented amongst those educated in poorly funded urban school and community resources systems (Orfield et al 2014;Atkins et al 2006). Many Latinx youth have limited access to adequate services due to limited mental health resources and lack of government funding for existing or new resources (DiPierro et al 2016;Acosta et al 2004). In particular, Puerto Ricans have shown higher signs of depression and anxiety (along with substance disorders and psychiatric disorders) in comparison to Mexicans, Cubans and other Latin American populations (Acevedo et al 2007).…”
Section: Mental Health Amongst Latinx Youthmentioning
confidence: 99%